Design and Implementation of Smart Parking Management System Based on RFID and Internet - Lanxin Wei; Qisheng Wu; Mei Yang; Wei Ding; Bo Li; Rong Gao (2012 International Conference on Control Engineering and Communication Technology, 2012)
In order to solve the ever-growing lack of parking space available, this paper designs and implements a smart parking management system based on the RFID (radio frequency identification) and internet. The system induces parking cars, each of which has the only RFID card, to park in right spaces of parking lots, and manages the information of parking cars there. Based on this, it can also help users query the information stored in database easily through the internet, which is designed in B/S architecture (Browser/Server architecture).